2015
DOI: 10.1089/ars.2014.5896
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed Flow Induces Autophagy, but Impairs Autophagic Flux to Perturb Mitochondrial Homeostasis

Abstract: Aim: Temporal and spatial variations in shear stress are intimately linked with vascular metabolic effects. Autophagy is tightly regulated in intracellular bulk degradation/recycling system for maintaining cellular homeostasis. We postulated that disturbed flow modulates autophagy with an implication in mitochondrial superoxide (mtO 2 -) production. Results: In the disturbed flow or oscillatory shear stress (OSS)-exposed aortic arch, we observed prominent staining of p62, a reverse marker of autophagic flux, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 83 publications
1
36
0
Order By: Relevance
“…In contrast, laminar flow reduces endothelial cell metabolism through Klf2-dependent repression of endothelial glycolytic enzymes [76] and promotes endothelial cell autophagy to protect endothelial cells from oxidant-induced cell injury [77, 78]. In contrast, oscillatory flow stimulates a JNK-dependent increase in mitochondrial superoxide production [79] but limits autophagy, allowing the accumulation of oxidant injury and markers of DNA damage (8-hydroxydeoxyguanosine) at sites of disturbed flow [78, 80]. Enhanced oxidant stress at sites of disturbed flow correlates with increased endothelial cell apoptosis [81], and disturbed flow promotes SUMOylation-dependent nuclear export of the apoptosis-regulating transcription factor p53, resulting in Bcl2 binding and induction of endothelial apoptosis [82].…”
Section: The Arterial Microenvironmental and Endothelial Activationmentioning
confidence: 99%
“…In contrast, laminar flow reduces endothelial cell metabolism through Klf2-dependent repression of endothelial glycolytic enzymes [76] and promotes endothelial cell autophagy to protect endothelial cells from oxidant-induced cell injury [77, 78]. In contrast, oscillatory flow stimulates a JNK-dependent increase in mitochondrial superoxide production [79] but limits autophagy, allowing the accumulation of oxidant injury and markers of DNA damage (8-hydroxydeoxyguanosine) at sites of disturbed flow [78, 80]. Enhanced oxidant stress at sites of disturbed flow correlates with increased endothelial cell apoptosis [81], and disturbed flow promotes SUMOylation-dependent nuclear export of the apoptosis-regulating transcription factor p53, resulting in Bcl2 binding and induction of endothelial apoptosis [82].…”
Section: The Arterial Microenvironmental and Endothelial Activationmentioning
confidence: 99%
“…The reason(s) for these discrepant observations is not clear, but may be related to different experimental settings. Interestingly, it has been noted that in the aortic arch, which is continuously exposed to turbulent or oscillatory shear stress, the level of the autophagy receptor protein p62 is upregulated, indicating an impaired autophagic flux . In cultured endothelial cells, although oscillatory shear stress significantly increases the abundance of LC3‐II and the number of autophagosome, these effects appear to be primarily due to blockade of the end stage autophagosome clearance, but not an enhanced induction of the autophagic response.…”
Section: Regulation Of Endothelial Autophagy By Mechanical Shear Stressmentioning
confidence: 99%
“…In cultured endothelial cells, although oscillatory shear stress significantly increases the abundance of LC3‐II and the number of autophagosome, these effects appear to be primarily due to blockade of the end stage autophagosome clearance, but not an enhanced induction of the autophagic response. In this case, the increased autophagosome accumulation to oscillatory shear stress is associated with increased oxidative stress, while further induction of autophagy by starvation or rapamycin normalises the disturbed redox homeostasis …”
Section: Regulation Of Endothelial Autophagy By Mechanical Shear Stressmentioning
confidence: 99%
“…Dysfunctional autophagy occurs when autophagy induction (autophagosome formation) becomes highly activated and, as a result, the autophagic flux (rate of autophagosome-lysosome fusion and degradation of autophagosomal cargo) slows down ('impaired' flux) leading to inadequate removal of dysfunctional mitochondria and a tonic increase in oxidative stress. Li et al [204] showed that OS exposure increases the induction of autophagy, but decreases the autophagic flux in cultured HAECs (whereas PS maintains autophagy at levels comparable to static controls); both the increased induction and decreased flux under OS were mediated by JNK activation and elevated mROS. The impaired EC autophagic flux was verified in OS-exposed regions of rabbit aortas [204].…”
Section: Mitochondrial Ca 2þ Uniporter: a Potential Therapeutic Targementioning
confidence: 99%
“…Li et al [204] showed that OS exposure increases the induction of autophagy, but decreases the autophagic flux in cultured HAECs (whereas PS maintains autophagy at levels comparable to static controls); both the increased induction and decreased flux under OS were mediated by JNK activation and elevated mROS. The impaired EC autophagic flux was verified in OS-exposed regions of rabbit aortas [204]. Graded inhibition of MCU activation in OS-exposed regions will reduce mROS, which, by lowering autophagy induction, should allow for, at least, partial normalization of the impaired flux, in agreement with a recent review [205].…”
Section: Mitochondrial Ca 2þ Uniporter: a Potential Therapeutic Targementioning
confidence: 99%